2018
DOI: 10.1002/ijc.31613
|View full text |Cite
|
Sign up to set email alerts
|

Low tumor infiltrating mast cell density confers prognostic benefit and reflects immunoactivation in colorectal cancer

Abstract: The role of mast cells (MCs) in colorectal cancer (CRC) progression was controversial. Thus, our study was designed to evaluate the prognostic value of MCs as well as their correlation with immune microenvironment. A retrospective cohort of CRC patients of stages I-IV was enrolled in our study. Consecutive patients (854) were divided into training set (427 patients) and validation set (427 patients) randomly. The findings were further validated in a GEO cohort, GSE39582 (556 patients). The mast cell density (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Consequently, the role of mast cells in pathogenesis has become a subject of raising interest. Especially, a growing body of evidence indicates that mast cells are implicated in tumor development [68][69][70][71][72][73]. Indeed, these cells are known to favor immunologic tolerance and secrete both growth and angiogenic factors which enhance tumor expansion [74][75][76].…”
Section: Mast Cells In Pathophysiology Of Hyperaldosteronismmentioning
confidence: 99%
“…Consequently, the role of mast cells in pathogenesis has become a subject of raising interest. Especially, a growing body of evidence indicates that mast cells are implicated in tumor development [68][69][70][71][72][73]. Indeed, these cells are known to favor immunologic tolerance and secrete both growth and angiogenic factors which enhance tumor expansion [74][75][76].…”
Section: Mast Cells In Pathophysiology Of Hyperaldosteronismmentioning
confidence: 99%
“…Previous studies confirmed the role of tumor-infiltrating immune cells in LUAD (43,44). A comprehensive characterization of immune cells in LUAD showed that CD8+ T cells accumulation is associated with a poor prognosis (45).…”
Section: Discussionmentioning
confidence: 68%
“…Research about the contribution of these cells to the modulation of TME remains largely unknown. Surveys into the implication of the cells in the TME has come to controversial findings acting as both pro‐ and antitumor cells (Mao et al, ). Negative correlation between MCs infiltration with the attraction of CD8 + T cells to the TME has been identified, in which low infiltration of MCs to the TME would lead to immunoactivation (Mao et al, ).…”
Section: Cells In the Tmementioning
confidence: 99%